Inovasi Pembuatan Cookies Sehat Dengan Penggunaan Stevia Pengganti Gula Dan Bubuk Daun Kelor, Bubuk Beetroot Serta Bubuk Bunga Telang Sebagai Pewarnanya - Fitri Liani Pramudhita (Universitas Kristen Indonesia Toraja, 2024)
O’Bites Cookies is an innovative product offering snacks with low sugar content and high nutrients, using natural ingredients such as stevia sugar, candlenuts, moringa leaves, and beetroot. The product comes in three flavor variants: butterfly pea flower, moringa leaves, and beetroot. The target market includes individuals who are health-conscious and looking to reduce sugar intake, especially those with obesity and diabetes. With the right marketing approach, O’Bites can become an attractive option for people concerned about their health. O’Bites engages in selling products to a health-conscious market aiming to reduce sugar consumption. Marketing the product to health-conscious markets also has the potential to increase revenue. Users can experience additional health benefits from butterfly pea flowers, moringa leaves, beetroot, and candlenut in cookies that can help stabilize blood sugar, aiding in diabetes control. The low sugar content of O’Bites Cookies makes it a suitable and healthy choice for snacking, allowing users to enjoy snacks while experiencing the benefits of additional natural ingredients. Additionally, the diverse flavor variants (butterfly pea flower, moringa leaves, and beetroot) provide variety and uniqueness to the product. O’Bites develops and combines existing cookie recipes with the use of natural ingredients, creating cookies in three flavor variants and packaging that makes it easy for consumers to store them back.